2011
DOI: 10.1167/iovs.11-7701
|View full text |Cite
|
Sign up to set email alerts
|

HumanCRB1-Associated Retinal Degeneration: Comparison with therd8 Crb1-Mutant Mouse Model

Abstract: CRB1 mutations lead to early-onset severe loss of vision with thickened, disorganized, nonseeing retina. Impaired peripheral vision can persist in late disease stages. Rd8 mice also have a disorganized retina, but there is sufficient photoreceptor integrity to produce largely normal retinal function. Differences between human and mouse diseases will complicate proof-of-concept studies intended to advance treatment initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 53 publications
12
101
2
1
Order By: Relevance
“…Small hyperreflective dots without shadowing, previously described by Aleman et al, 12 were found in the inner and outer retinal layers at different depths from the vitreoretinal surface in 11 of 11 patients (100%; Fig 4AeD). The origin of these hyperreflectivities was unclear.…”
Section: Findings On Retinal Imagingsupporting
confidence: 67%
See 4 more Smart Citations
“…Small hyperreflective dots without shadowing, previously described by Aleman et al, 12 were found in the inner and outer retinal layers at different depths from the vitreoretinal surface in 11 of 11 patients (100%; Fig 4AeD). The origin of these hyperreflectivities was unclear.…”
Section: Findings On Retinal Imagingsupporting
confidence: 67%
“…Previous reports have found Coats-like exudates in 0% to 25%. 12,17,18,29 Full-field electroretinography responses became unrecordable on average in the second decade of life in 50% of our RP cohort and in the first decade of life in our LCA cohort, with high intrafamilial and interfamilial variability in the RP group. These electroretinography results indicate that most patients with CRB1-associated RP and LCA are affected by early panretinal rod and cone dysfunction.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations